The protective effect of Blautia coccoides in secondary injury of intracerebral hemorrhage - Shao, Xian; Zheng, Matao; Ye, Chenglong; Lu, Jiafeng; Li, Mengyun; Su, Kuiwei; Lin, Hui; He, Lingyan; Qi, Xuchen; Wang, Jianli (Frontiers in Microbiology, 2025)
Intracerebral hemorrhage (ICH) is a severe stroke with high rates of disability and mortality. Emerging evidence suggests a link between neurological disorders and gut microbiota dysbiosis, though the underlying mechanisms remain unclear. To investigate the role of gut microbiota in ICH, we conducted metagenomic analysis of fecal samples from 35 healthy individuals and 36 patients with ICH, including 29 survivors and seven deceased patients. Metagenomic analysis revealed decreased gut microbiota diversity in patients with ICH, with Blautia genus identified as potential biomarkers. We also established an ICH mouse model via stereotactic autologous blood injection to assess the therapeutic potential of Blautia genus. Blautia coccoides (BC), a representative strain, improved neurofunctional outcomes in ICH mice, reduced tissue damage and neuronal apoptosis, and decreased glial cell activation markers (GFAP and Iba1). BC treatment also lowered the serum levels of pro-inflammatory cytokines (TNF-α, IL-6, and IL-1β) and partially restored gut microbial homeostasis. These findings suggest that BC plays a crucial role in ICH progression and may serve as a potential therapeutic agent by modulating gut microbiota. Further research and clinical trials are necessary to validate its efficacy and safety in humans.